Translations of Yarliqs of the Crimean khans to the Jewish Community of Kyrk-Yer (Chufut-Kale) in the Archives of the Russian Federation (According to the Materials of the State Archive of the Republic of Crimea and the Russian State Historical Archive) - Prokhorov D.A. (Золотоордынское обозрение)
Research objectives: Introduction of archival materials for the history of the Jewish communities of Crimea in the Middle Ages and Modern Times into scientific discourse. Research materials: Study of funds of the Russian State Historical Archives (RGIA, St. Petersburg) and State Archives of the Republic of Crimea (GARK, Simferopol) resulted in the introduction of the materials related to the history of the Karaite community of Kyrk-Yer (Chufut-Kale) into scientific discourse. This includes little-known translations of yarliqs and fermans, securing the legal and economic status, issued at different times by the Crimean khans to representatives of the Karaite community. The translations into Russian were made in the second half of the nineteenth – early twentieth century by representatives of Russian academic circles, orientalists, historians, as well as officials of the institutions of the Taurida Governorate. Results and scientific novelty: The study considers a number of little-known documents related to the history of the Crimean Khanate, found in the archival collections of the Russian Federation. One of the earliest translations into Russian of the yarliq of the Crimean Khan Selyamet-Girey I (1608) from the collection of the Russian orientalist and statesman V.V. Grigoriev was discovered in fund No. 853 “Vasily Vasilyevich Grigoriev (1816–1881), professor of the history of the East of St. Petersburg University, governor of the Orenburg Kirghiz region, head of the Main Directorate for Press Affairs of the Russian State Historical Archive (RGIA)”. This document is particularly important because its original has not survived. Additionally, materials of the fund 241 “Taurida and Odessa Karaite Spiritual Government” of the State Archive of the Republic of Crimea (GARK) were found to contain documents, reporting the translations of the decisions of the “Kadiasker court”, as well as fermans to the Kyrk-Yer Jewish community of khans: Saadet-Girey I (1524), Inayet-Girey (1635), Mohammed-Girey IV (1642), Murad-Girey (1678–1683) and Saadet-Girey IV (1717–1724). The appendices to the article contain the full texts of the translations of the khan’s fermans into Russian made in the late 19th – early 20th centuries with the participation of prominent Russian orientalists. These documents are a valuable source for the scientific reconstruction of the past of the old nations of the Crimean peninsula in the Middle Ages and Modern Times, as well as the economic and legal life of representatives of various categories of the communities of the Crimean Khanate.